Thermal performance of unfired clay bricks used in construction in the north of France: Case study - Fayçal El Fgaier; Zoubeir Lafhaj; Franck Brachelet; Emmanuel Antczak; Christophe Chapiseau (Case Studies in Construction Materials, 2015)
The objective of this study is to demonstrate and to study the sustainability and the qualities of the earthen construction in real conditions. A demonstrative building was designed and built with unfired clay bricks, were industrially produced by the factory “Briqueteries du Nord” (BdN). This industrial plant is located in the north of France. This project aims to create conditions for the development of earthen construction techniques in the north of France. Moreover, it aims to prove the benefits of this material on the sanitary quality of the building. This article is composed of three parts. Firstly, the identification of raw materials was performed in order to study the mains properties of these building materials. The second part of this work presented an experimental study conducted to investigate the dynamic thermal performance of unfired clay bricks. To complete the tests already carried out in laboratory, an experimental investigation was carried out in situ on a demonstrative building. The hygrothermal performance of building is monitored for two consecutive years. The first analysis of the obtained data proved clearly that the earthen wall reduces the fluctuations of the outside temperature.